2022
DOI: 10.3390/cells11132009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Retinoic Acid-Inducible Gene I Overexpression Reveals the Potential Genes for Autophagy-Related Negative Regulation

Abstract: Retinoic acid-inducible gene I (RIG-I) serves as an essential viral RNA sensor for innate immune. The activation of the RIG-I-like receptors (RLRs) pathway triggers many regulations for the outcome of type I interferon, including ubiquitination, dephosphorylation, ISGylation, and autophagy. However, the autophagy-related regulation of RIG-I is still not fully understood. To investigate the potentially unknown genes related to autophagy-related regulation of RIG-I, we firstly confirm the induction of autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Our lab and a recent study have reported that the innate immune-associated molecules, RIG-I, could be degraded by autophagy [ 20 , 21 ]. Additionally, RIG-I is an important sensor for RNA viruses to trigger the interferon response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our lab and a recent study have reported that the innate immune-associated molecules, RIG-I, could be degraded by autophagy [ 20 , 21 ]. Additionally, RIG-I is an important sensor for RNA viruses to trigger the interferon response.…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has proved that feline RIG-I plays an essential role in the antiviral effect of FCV infection (not shown in this study). Moreover, our previous study indicated that autophagy could negatively regulate RIG-I [ 20 ]. In this study, we found that FCV infection triggered autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the ZIKV NS5 protein inhibited RNA-mediated RIG-I IFN production in HEK-Lucia™ RIG-I cells (Figure 5a, compared with cells not expressing NS5), a model for measuring IFN production in a 5' triphosphate hairpin RNA (3p-hpRNA) RIG-I agonist-dependent manner [159][160][161][162]. In the presence of 3-MA, NS5 completely abrogated the IFN response mediated by the RIG-I agonist 3p-hpRNA (Figure 5a).…”
Section: Autophagy Controls the Stability Of The Zikv Ns5 Protein And...mentioning
confidence: 98%
“…We observed that the ZIKV NS5 protein inhibited RNA-mediated RIG-I IFN production in HEK-Lucia™ RIG-I cells (Figure 5a, compared with cells not expressing NS5), a model for measuring IFN production in a 5 ′ triphosphate hairpin RNA (3p-hpRNA) RIG-I agonist-dependent manner [159][160][161][162]. In the presence of 3-MA, NS5 strongly diminished the IFN response mediated by the RIG-I agonist 3p-hpRNA (Figure 5a).…”
Section: Autophagy Controls the Stability Of The Zikv Ns5 Protein And...mentioning
confidence: 99%